2001
DOI: 10.1051/0004-6361:20010436
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Deep VLT spectroscopy of the $\vec{z}=$ 2.49 radio galaxy MRC 2104-242

Abstract: Abstract. We present spectroscopic observations of the rest-frame UV line emission around radio galaxy MRC 2104-242 at z = 2.49, obtained with FORS1 on VLT Antu. The morphology of the halo is dominated by two spatially resolved regions. Lyα is extended by >12 along the radio axis, C IV and He II are extended by ∼8 . The overall spectrum is typical for that of high redshift radio galaxies. The most striking spatial variation is that N V is present in the spectrum of the region associated with the center of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Our detection of the quiescent Lyα halo of 2104−242 (Overzier et al 2001; Villar‐Martín et al 2003) in the light of [O iii ]λ5008 and Hα shows that this halo is ionized, and is not merely neutral gas acting as a Lyα mirror. Similarly, by way of detection of [O ii ]λ3728, [O iii ]λ5008 and Hα, we have shown that the giant Lyα halo of 4C+10.48 (see van Ojik et al 1997) is ionized.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Our detection of the quiescent Lyα halo of 2104−242 (Overzier et al 2001; Villar‐Martín et al 2003) in the light of [O iii ]λ5008 and Hα shows that this halo is ionized, and is not merely neutral gas acting as a Lyα mirror. Similarly, by way of detection of [O ii ]λ3728, [O iii ]λ5008 and Hα, we have shown that the giant Lyα halo of 4C+10.48 (see van Ojik et al 1997) is ionized.…”
Section: Discussionmentioning
confidence: 85%
“…We suggest that He ii λ1640/Hβ can be used to make a first order estimate of A v when Hα/Hβ and He ii λ1640/He ii λ4687 are not available. In addition, we have identified several new line ratios to calculate electron temperature: [Ne v ]λ1575/[Ne v ]λ3426, [Ne iv ]λ1602/[Ne iv ]λ2423, O iii ]λ1663/[O iii ]λ5008 and [O ii ]λ2471/[O ii ]λ3728. Using O iii ]λ1663/[O iii ]λ5008 we have calculated an average T e of 14100 +1000 −600 K. Our detection of the quiescent Lyα halo of 2104−242 (Overzier et al 2001; Villar‐Martín et al 2003) in the light of [O iii ]λ5008 and Hα shows that this halo is ionized, and is not merely neutral gas acting as a Lyα mirror. Similarly, by way of detection of [O ii ]λ3728, [O iii ]λ5008 and Hα, we have shown that the giant Lyα halo of 4C+10.48 (see van Ojik et al 1997) is ionized.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Another possibility is that the Lyα emission arises from gas associated with the debris of massive mergers that is being illuminated by the AGN (Yajima et al, 2013;Yang et al, 2014;Hennawi et al, 2015;Johnson et al, 2015). Lyα halos and LABs often show substantial chemical enrichment (De Breuck et al, 2000;Overzier et al, 2001;Prochaska & Hennawi, 2009;Hennawi et al, 2015), which would perhaps be most easily explained by the outflow or merger scenario, rather than a scenario where the gas originates from the IGM.…”
Section: Protoclusters and Lyα Blobsmentioning
confidence: 99%